RAR: Retrieval Augmented Retrieval for Code Generation in Low Resource Languages - Dutta, Avik; Singh, Mukul; Gulwani, Sumit; Le, Vu; Verbruggen, Gust (EMNLP 2024, 2024)
Language models struggle in generating correct code for low resource programming languages, since these are underrepresented in training data. Popular approaches use either examples or documentation to improve the performance of these models. Instead of considering the independent retrieval of this information, we introduce retrieval augmented retrieval (RAR) as a two-step retrieval method for selecting relevant examples and documentation. Extensive experiments on two low resource languages (Power Query M and OfficeScript) show that RAR outperforms example or grammar retrieval techniques (2.81–26.14%).